2011
DOI: 10.1007/bf03404873
|View full text |Cite
|
Sign up to set email alerts
|

Exploring School Oral Health Outcomes and Neighbourhood Factors in Schools Participating in Ontario’s “Healthy Schools” Recognition Program

Abstract: Objectives: This ecologic study compared school-level oral health outcomes in schools participating in Ontario's "Healthy Schools" program and nonparticipating schools in York Region, Ontario in 2007-2008 and examined the effect of neighbourhood socio-economic factors.Method: School-aggregated data were obtained for all 243 elementary schools. York Region Public Health Unit provided oral health data from school dental screenings. We obtained information about schools participating in the Ontario's "Healthy Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…A detailed evaluation of an HPS initiative in Brazil indicated positive effects on the level of dental caries and orofacial trauma among pupils attending schools with oral-health-supportive policies (179). Similar effects were reported by Ontario HPS initiatives launched in 2006 (189). A published review of HPS that targeted more than one health outcome only identified nine studies that met the review criteria and none had been conducted in African schools (190).…”
Section: Evaluation Of Oral Health Promotion Programsmentioning
confidence: 74%
“…A detailed evaluation of an HPS initiative in Brazil indicated positive effects on the level of dental caries and orofacial trauma among pupils attending schools with oral-health-supportive policies (179). Similar effects were reported by Ontario HPS initiatives launched in 2006 (189). A published review of HPS that targeted more than one health outcome only identified nine studies that met the review criteria and none had been conducted in African schools (190).…”
Section: Evaluation Of Oral Health Promotion Programsmentioning
confidence: 74%
“…Schools provide ideal environments for oral health promotion interventions, offering efficient and effective ways to reach adolescents and consequently was where most of the interventions were conducted. The World Health Organization's Health Promoting Schools initiative has been shown to have some success here 54,55 . These holistic programmes may be more effective as they integrate elements of social and physical environmental factors and policy development 55 …”
Section: Discussionmentioning
confidence: 99%
“…Foremost among potential policy solutions are efforts focused on improving the nutritional quality of children's diets in schools and their surrounding neighborhoods (19, 35). Indeed, healthy eating environments may have effects beyond obesity reduction, benefitting children's oral health (19, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Only 4 studies found in the published literature examined multilevel interventions on children's oral health, and thus were better able to assess impacts on oral health equity (19, 3537) (Table 1). An ecological study was conducted in the York Region of Ontario, Canada that compared school-level oral health outcomes in elementary schools participating in Ontario's Healthy Schools recognition program and non-participating schools, and examined the effect of neighborhood socioeconomic status on oral health outcomes (35). A second multilevel Canadian study examined oral health promoting school environments and dental caries in Québec children using data from a cohort study that recruited white children at risk of obesity and their families from Greater Montreal schools (19).…”
Section: Selected Models Of Evaluated School-based Oral Health Programsmentioning
confidence: 99%
See 1 more Smart Citation